Technology from hunting blinds: A study of lithic assemblages in Late Holocene stone structures from Patagonia (Argentina) - Flores Coni, Josefina (2023)
Stone structures called parapetos are a highlighted feature of the archaeological record in central-western Santa Cruz, Patagonia. More than 500 have been registered so far with varied sizes and shapes and clustered in different amounts. They are located in basaltic plateaus, over 700 masl. These hunter-gatherer structures are believed to be mainly related to hunting activities though some sites have revealed a more general function. Radiocarbon dates reveal that they are a typical Late Holocene technology.This work discusses the characteristics of lithic materials recovered in these particular sites with a specific spatial and temporal distribution in Patagonia. We evaluate the existence of variability in lithic artefacts related to stone structures recovered in different areas: Pampa del Asador (Cerro Pampa), Guitarra Plateau, Asador Plateau and the Strobel Plateau. Diverse types of hunting blind sites have been included: isolated structures and grouped ones located in different topographic and ecological contexts. Materials were recovered from inner and outer surfaces of structures as well as from stratigraphic contexts. The sample includes tools, debitage and cores; more than 10000 lithic artefacts are included.Results show that there are similarities in the characteristics of artefacts discarded in parapetos from different areas. However, variability in the type and characteristics of artefacts in each assemblage could account for a wider array of activities being carried out in parapetos from the northern sector of the region under study. Thus, strategies for occupying highlands during the Late Holocene differed.The evidence discussed summarises more than 20 years of on-going investigations in the region. It provides exceptional information based on systematic analysis of a significant sample of lithic artefacts in hunting blinds.